Menjaga Kesehatan Anak dengan Minuman Moringa Latte sebagai Upaya Pencegahan Stunting: Maintaining Children's Health with Moringa Latte Beverage as a Stunting Prevention Effort - Sriarumtias, Framesti Frisma; Syamsudin, Raden Aldizal Mahendra Rizkio; Asysyarip, Siti Maryam; Maulidini, Anida Almalia; Ayudia, Sarah Azka; Wardhani, Pramudita Tiara Kusuma; Triana, Daina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Stunting is a global issue that affects various regions in Indonesia, including Garut. In response to this, our team from the Pharmacy Program at Garut University organized a training program on making healthy moringa latte beverages in the village of Panyindangan, Cisompet sub-district, Garut Regency. The primary objective of this training is to empower homemakers with knowledge and skills to create nutritious snacks for their children using natural ingredients, mainly known as garden produce, that can prevent stunting, which moringa leaves. As a result of this initiative, community members gained a deeper understanding of harnessing the nutritional value of moringa latte beverages. Children readily accept this beverage due to its attractive color, appealing shape, and delicious taste.